2009
DOI: 10.1073/pnas.0901679106
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of nucleoside diphosphate kinase B with Gβγ dimers controls heterotrimeric G protein function

Abstract: Heterotrimeric G proteins in physiological and pathological processes have been extensively studied so far. However, little is known about mechanisms regulating the cellular content and compartmentalization of G proteins. Here, we show that the association of nucleoside diphosphate kinase B (NDPK B) with the G protein ␤␥ dimer (G␤␥) is required for G protein function in vivo. In zebrafish embryos, morpholino-mediated knockdown of zebrafish NDPK B, but not NDPK A, results in a severe decrease in cardiac contrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
73
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 26 publications
(45 reference statements)
6
73
0
Order By: Relevance
“…Knockdown of NDPK-C also reduces cAMP production, which is consistent with the essential role of NDPK-C mediating the interaction between G proteins and NDPK-B. 39 Knockdown of NDPK-B in zebrafish also reduces G-protein expression, with a similar phenotype as the Gβ 1 /Gβ 1-like knockdown zebrafish, 41 suggesting that, in addition to acute regulation of G-protein activity, long-term modulation of NDPKs may influence the protein levels of G proteins, possibly because of the membrane-targeting effects of NDPK complexes. Consistently, studies in neonatal rat cardiomyocytes have shown that NDPK-B and NDPK-C critically regulate the membrane localization of G proteins.…”
Section: Relevance Of Ndpk-mediated Regulation Of G-protein Signalingsupporting
confidence: 58%
See 1 more Smart Citation
“…Knockdown of NDPK-C also reduces cAMP production, which is consistent with the essential role of NDPK-C mediating the interaction between G proteins and NDPK-B. 39 Knockdown of NDPK-B in zebrafish also reduces G-protein expression, with a similar phenotype as the Gβ 1 /Gβ 1-like knockdown zebrafish, 41 suggesting that, in addition to acute regulation of G-protein activity, long-term modulation of NDPKs may influence the protein levels of G proteins, possibly because of the membrane-targeting effects of NDPK complexes. Consistently, studies in neonatal rat cardiomyocytes have shown that NDPK-B and NDPK-C critically regulate the membrane localization of G proteins.…”
Section: Relevance Of Ndpk-mediated Regulation Of G-protein Signalingsupporting
confidence: 58%
“…Consistently, studies in neonatal rat cardiomyocytes have shown that NDPK-B and NDPK-C critically regulate the membrane localization of G proteins. 39,41 Moreover, acute stimulation of rat cardiomyocytes overexpressing NDPK-C with the β-adrenoceptor agonist isoprenaline results in enhanced membrane localization of G proteins and NDPK-C, 39 suggesting that recruitment of NDPK/G protein complexes to the plasma membrane may counteract a fading response to long-term isoprenaline stimulation due to desensitization of β-adrenoceptors.…”
Section: Relevance Of Ndpk-mediated Regulation Of G-protein Signalingmentioning
confidence: 99%
“…Re-expression of human NME2 in KO MEFs rescued the loss in G protein content and restored basal cAMP levels [104]. The Wieland laboratory showed that heart failure is associated with similar defects and in zebrafish, where morpholino-mediated knockdown of NME2, as well as Gb1, both resulted in dramatically reduced cardiac contractility (Fig.…”
Section: Nm23-x4 Function In Xenopus Retinal Developmentmentioning
confidence: 90%
“…1d). They suggested that decreased asubunit abundance alters adenylyl cyclase-regulating Gs and Gi protein subfamilies [104]. These defects were also rescued by injection of zebrafish Nme2 mRNA into morphants.…”
Section: Nm23-x4 Function In Xenopus Retinal Developmentmentioning
confidence: 99%
See 1 more Smart Citation